Multiplexed Lateral Flow Test for Detection and Differentiation of Cronobacter sakazakii Serotypes O1 and O2 - Scharinger, Eva J.; Dietrich, Richard; Wittwer, Tobias; Märtlbauer, Erwin; Schauer, Kristina (Frontiers in Microbiology, 2017)
The ubiquitous and opportunistic pathogen Cronobacter sakazakii is responsible for severe meningitis, sepsis, and necrotizing enterocolitis in neonates and infants associated with ingestion of contaminated powdered infant formula (PIF). The current ISO method for isolation and detection of Cronobacter spp. is laborious, time-consuming and expensive. In this study, a multiplexed lateral flow test strip was developed to rapidly detect and simultaneously serotype O1 and O2 C. sakazakii serotypes. The assay is based on two monoclonal antibodies (MAb) that specifically bind to the lipopolysaccharides (LPS) of these pathogens. The test strip provides results very quickly; C. sakazakii could be detected in pure culture within 15 min with a sensitivity of 107 CFU/ml. After non-selective enrichment for 18 h as low as one Cronobacter cell per g PIF could be detected. Moreover, the established lateral flow assay (LFA) offers excellent specificity showing no cross-reactivity with other C. sakazakii serotypes, Cronobacter species or Enterobacteriaceae tested. These characteristics, together with several advantages such as speed, simplicity in performance, low analysis cost, and no requirement of specialized skills or sophisticated equipment make the developed multiplexed LFA suitable for reliable detection and serotyping of C. sakazakii serotypes O1 and O2.